Water Soluble Polysaccharide Yellow Bentul (Colocasia Esculenta Schott [L]) As a Candidate for Antidiabetic Agent - Sentot Joko Raharjo; Mahisa Ayyuna Nailufar; Ambar Fidyasari; Erik Widarto (Published by Faculty of Medicine Universitas Islam Malang, 2017)
ABSTRACTIntroduction: Yellow bentul tuber is one of tuber plant species which have bioactive compound of Water Soluble Polysaccharide (WSP) and potentially healthy nutrition in the therapy of metabolic syndrome disease. The purpose of this research is to prove the ability of WSP isolate to reduce blood glucose level in white mice. Methods: The yield determination of yellow bentul tube flour, yield of WSP isolates yellow bentul tuber using enzymatic method, WSP identification using HPLC with Aminex HPX-87C BIORAD5 columns, and antidiabetic activity test using white mices. Test activity was performed in six treatment groups (Normal, Induction STZ 20 mg/ kgBW, Induction STZ 20 mg / kgBW + metformin 195mg / KgBW, three treatment with STZ induction 20 mg/ kgBW and WSP isolate with concentration 200, 400, and 600mg / kgBB). Determination of blood glucose levels using glucometer and supported by observation of histologic improvement of beta pancreatic cells in white mice that have necrosis. Result: The yield of yellow bentul flour was 14%. Yield WSP isolates of yellow bentul was 4.18%. WSP levels obtained 96.91%. Blood glucose level induced by STZ 20mg/ kgBW mice decreased glucose level at 400mg/ kgBW dose in the second week and histologic improvement of beta pancreatic cells that has the most optimal necrosis at a WSP dose of 200 mg/ kgBW. Conclusion: Isolate of Water Soluble Polysaccharide of yellow bentul potentially lower blood sugar level.Kata Kunci:, Water-soluble Polysaccharides, yellow bentul tuber, antidiabetic